Rescue Diverting Loop Ileostomy: An Alternative to Emergent Colectomy in the Setting of Severe Acute Refractory IBD-Colitis. Issue 2 (February 2018) - Russell, Tara A.; Dawes, Aaron J.; Graham, Danielle S.; Angarita, Stephanie A.K.; Ha, Christina; Sack, Jonathan
Abstract : BACKGROUND: Severe acute refractory colitis has traditionally been an indication for emergent colectomy in IBD, yet under these circumstances patients are at elevated risk for complications because of their heightened inflammatory state, nutritional deficiencies, and immunocompromised state. OBJECTIVE: We hypothesized that rescue diverting loop ileostomy may be a viable alternative to emergent colectomy, providing the opportunity for colonic healing and patient optimization before more definitive surgery. DESIGN: This was a retrospective case series. SETTINGS: The study was conducted at a single academic center. PATIENTS: Patients with severe acute medically refractory IBD-related colitis were included. INTERVENTION: Rescue diverting loop ileostomy was the intervening procedure. MAIN OUTCOME MEASURES: The primary outcome was avoidance of urgent/emergent colectomy. The secondary outcome was efficacy, defined by 3 clinical aims: 1) reduced steroid dependence or opportunity for bridge to medical rescue, 2) improved nutritional status, and 3) ability to undergo an elective laparoscopic definitive procedure or ileostomy reversal with colon salvage. RESULTS: Among 33 patients, 14 had Crohn's disease and 19 had ulcerative colitis. Three patients required urgent/emergent colectomy, 2 with ulcerative colitis and 1 with Crohn's disease. Across both disease cohorts, >80% of patients achieved each clinical aim for efficacy: 88% reduced their steroid dependence or were able to bridge to medical rescue, 87% improved their nutritional status, and 82% underwent an elective laparoscopic definitive procedure or ileostomy reversal. A total of 4 patients (11.7%) experienced a postoperative complication following diversion, including 3 surgical site infections and 1 episode of acute kidney injury. LIMITATIONS: The study was limited by being a single-center, retrospective series. CONCLUSIONS: Rescue diverting loop ileostomy in the setting of severe, refractory IBD–colitis is a safe and effective alternative to emergent colectomy. This procedure has acceptably low complication rates and affords patients time for medical and nutritional optimization before definitive surgical intervention. SeeVideo Abstract athttp://links.lww.com/DCR/A520 .